The possibility of polymorphonuclear leukocyte activation in dental socket healing by freeze-dried Aloe vera induction - Pratiwi Soesilawati; Ester Arijani Rachmat; Ira Arundina; Nita Naomi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: Research has proved that Aloe vera has anti-inflammatory, anti-bacterial, and immunomodulator properties that can accelerate the healing process. These properties could be beneficial in the tooth extraction wound-healing process. Neutrophils are the first inflammatory cells to invade and are the predominant cell markers in the wound for 24 hours after injury. Polymorphonuclear leukocytes (PMN) provide initial protection against micro-organisms, as they engulf and digest foreign bodies. Purpose: The aim of this study was to prove the effect of Aloe vera 90% gel application on the PMN count in the healing process of Cavia cobaya following tooth extraction. Methods: This laboratory experimental research was done using Post-Test Only Control Group Design. The lower incisive of twelve male Cavia cobayas were extracted then divided into four groups. Group P1 and P3 had 90% Aloe vera gel applied into the socket and sutured; group K1 and K3, received no 90% Aloe vera gel application and acted as controls. Samples from group P1 and K1 were terminated and had their mandibula taken one day after tooth extraction, and those from group P3 and K3 were terminated after three days. Tissues were then processed into histology slides, and PMN cells were counted. Results: There were significant differences in the PMN count between groups K1, P1, and K3 compared with P3 (p < 0.05). Higher PMN count was shown on the group containing Aloe vera 90% gel compared with control group, both on day one and three after tooth extraction. Conclusion: Aloe vera 90% gel can increase the PMN count in the inflammation phase of the tooth extraction wound-healing process.